Physiological behavior of Genipa americana L. seeds regarding the capacity for desiccation and storage tolerance - Magistrali, Paulo Roberto; José, Anderson Cleiton; Faria, José Marcio Rocha; Gasparin, Ezequiel (Journal of Seed Science, 2013)
Knowledge of the capacity of desiccation and storage tolerance of seeds is essential to provide adequate conditions necessary to maintain viability after seed collection. Drying rate is one of the factors which have been described as affecting the physiological response of seeds of various species. Literature reports that Genipa americana seeds exhibit an intermediate behavior, quickly losing viability if stored at negative temperatures. Thus, this work aimed to verify the effect of slow drying over the capacity of desiccation and storage tolerance of Genipa americana seeds. Seeds with 47% of water content (recently harvested) were dried over salt solutions until reaching 30%, 20%, 15%, 10% and 5% of water content. After drying to 10% and 5% of water content a reduction in seed viability was observed after 30 days of storage without the total loss of germination after three months in these conditions. The slow drying increased the capacity for desiccation and storage tolerance of the Genipa americana seeds if compared to the information described in literature.

Conhecer a capacidade de tolerância à dessecação e ao armazenamento das sementes tem sido imprescindível para disponibilizar condições adequadas para a manutenção da viabilidade após a coleta. A velocidade de secagem é um dos fatores que tem influenciado na resposta fisiológica das sementes de diversas espécies. Deste modo, buscou-se verificar o efeito da secagem lenta na capacidade de tolerância à dessecação e ao armazenamento das sementes de Genipa americana L. Sementes com 47% de umidade (recém-colhidas) foram secas em soluções salinas até 30, 20, 15, 10 e 5% de umidade, testando-se a viabilidade. Ao atingir 10 e 5% de umidade as sementes foram armazenadas a -20 ºC, avaliando-se a viabilidade a cada 30 dias durante três meses. Sementes recém-colhidas apresentaram 98% de germinação sem perda de viabilidade até 10% de umidade. Sementes secas a 10 e 5% de umidade apresentaram redução na viabilidade após 30 dias de armazenamento, porém não houve a perda total de germinação após este período. A secagem lenta aumentou a capacidade de tolerância à dessecação e ao armazenamento das sementes de Genipa americana se comparada às informações descritas na literatura.
Keywords: Physiological classification; Brazilian forest species; Genipapo plants; Classificação fisiológica; Espécie florestal brasileira; Jenipapeiro